Teacher’s Strategy in Teaching Writing Descriptive Text Using Whatsapp Applicationat Smp N 3 Medan - Rade Tri Putri Bancin; Indra Hartoyo (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
This research focused on the descriptive text teaching teaching teachingtext using the WhatsApp application. This study was limited to the writingof a descriptive text in which the descriptive text was considered for theteacher's education. Limited to the strategies used by a teacher class masterin the seventh grade. The education focus is the descriptive text for theseventh degree of SMP N 3 Medan. The question of this research is one ofthe teachers at high school, in particular the English teacher of the seventhgrade at SMP N 3 Medan. This turned research was qualitative descriptivewith direct observation, interviewed. Data analysis shows that the teacherof SMP N 3 Medan applied two learning strategies by teaching online evenif only a part of the two strategies have been used. The strategies that theteacher used in teaching the descriptive writing used by the teacher weretwo strategies, imaginary strategy and strategy of scaffolding. The purposeof this strategy was to make the material understand the material. Also,when using this strategy, the teacher can get students independently inwriting and increase the students who understood the material. Inscaffolding strategy, the professor trained students to think independently.When you think independently, students could end up at home, studentshave done at home and made a writing description of the product on theirfavorite and then discussed together when the class online process.